2002
DOI: 10.14411/eje.2002.075
|View full text |Cite
|
Sign up to set email alerts
|

The ant-associations and diet of the ladybird Coccinella magnifica (Coleoptera: Coccinellidae)

Abstract: Abstract. The ladybird Coccinella magnifica is typically considered to be myrmecophilous, and primarily associated with the For mica rufa group of wood ants. It is regularly associated with ants of the F. rufa group in north-western Europe. The very limited data on the habitat preference of C. magnifica in the southern and eastern parts of its range indicate that its ant-associations change and that it may even be non-myrmecophilous in this region. C. magnifica might consist of geographically restricted specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Indeed, during prey shortages, the limited availability of untended colonies might have forced ladybirds to prey on ant-tended colonies, opening the path to developing a tolerance towards ant aggressiveness. However, the myrmecophily of C. magnifica ladybirds has not been observed throughout its European habitat, suggesting that Thalassa saginata Dolichoderus bidens Unknown Ant mimicry [32] myrmecophily might be facultative or limited to some populations [45]. Concerning oviposition, two strategies have been observed.…”
Section: Behavioural Traitsmentioning
confidence: 99%
“…Indeed, during prey shortages, the limited availability of untended colonies might have forced ladybirds to prey on ant-tended colonies, opening the path to developing a tolerance towards ant aggressiveness. However, the myrmecophily of C. magnifica ladybirds has not been observed throughout its European habitat, suggesting that Thalassa saginata Dolichoderus bidens Unknown Ant mimicry [32] myrmecophily might be facultative or limited to some populations [45]. Concerning oviposition, two strategies have been observed.…”
Section: Behavioural Traitsmentioning
confidence: 99%
“…Some habitat-specific coccinellids still consume a relatively high diversity of prey. For example, Coccinella magnifica, which is restricted to the vicinity of Formica rufa ant colonies in Britain, consumes a wide diversity of aphid prey in its specialized habitat (Sloggett et al, 2002): thus in my dichotomy C. magnifica is considered a generalist. Species sizes were obtained as body lengths from Iablokoff-Khnzorian (1982): as a range of sizes are given for each species I used the median value for each size range.…”
Section: A Test Of the Body Size-dietary Breadth Hypothesismentioning
confidence: 99%
“…Schulenburg & J.J. Sloggett, unpub. data) and are ecol ogically similar in a number of respects (Sloggett et al, , 2002. However C. septempunctata is not a myrmecophile, although the adults of this species will sometimes visit colonies of ant-tended aphids when prey is scarce in late summer (Sloggett & Majerus, 2000).…”
Section: Introductionmentioning
confidence: 95%
“…Arnold et al (unpublished, see Majerus, 1994, p. 151) have observed that C. magnifica larvae placed on colonies of Aphis fabae Scopoli tended by the ant Lasius niger (L.) are attacked by the ants, but the larvae ignore these attacks, continuing to feed and behave normally. Coccinella magnifica is not associated with L. niger naturally (Sloggett et al, 2002).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation